Saliva fatigue biomarker index as a marker for severe myalgic encephalomyelitis/chronic fatigue syndrome in a community based sample. Issue 4 (2nd October 2021) - Jason, Leonard A.; Kalns, John; Richarte, Alicia; Katz, Ben Z.; Torres, Chelsea
ABSTRACT : Objective: The prevalence of pediatric Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) has been estimated from an ethnically and sociodemographically diverse community-based random sample of 10, 119 youth aged 5–17. We assessed whether a salivary biomarker of fatigue could identify youth with ME/CFS. Study design: We examined the ratio of the concentrations of 2 peptide fragments in saliva, referred to as the Fatigue Biomarker Index (FBI), in participants from our study diagnosed with ME/CFS ( n  = 59) and matched controls ( n  = 39). Results: Significant overall differences were found in the FBI between those participants with severe ME/CFS and those with ME/CFS and the controls. Conclusions: If confirmed in other populations, the FBI could serve as an objective test to aid in the diagnosis of severe ME/CFS. Abbreviations : ANOVA: analysis of variance; BSA: bovine serum albumin; FBI: fatigue biomarker index; IM: infectious mononucleosis; ME/CFS: myalgic encephalomyelitis/chronic fatigue syndrome; OF: oral fluid; S-ME/CFS: severe myalgic encephalomyelitis/chronic fatigue syndrome